Botulinum toxin type A in postherpetic neuralgia at the craniofacial region: A case report and literature review (2019)
Postherpetic neuralgia in the facial region is a frequent and disabling clinical condition, characterized by the presence of neuropathic pain for more than 3 months after the outbreak of herpes zoster. Pain control is sometimes inadequate and the adverse effects of the interventions are deleterious to the health of patients, with an impact on their quality of life. In this paper we present the case of a 70-year-old woman with complaint of neuropathic pain secondary to herpes zoster in the orofacial region, who was refractory to conventional treatments and responded to the application of botulinum toxin type A. Botulinum toxin type A is a therapeutic strategy that has been used in recent years for the management of postherpetic neuralgia with adequate response, as recorded in case reports and 2 randomized clinical trials. The present case and those available in literature support the use of botulinum toxin type A in postherpetic neuralgia in the facial region, as a tolerable, safe and effective therapeutic strategy. © 2017 Sociedad Neurológica Argentina